Use of a composite microneedle

CN122998591APending Publication Date: 2026-10-30CHONGQING UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202611405658.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-10
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

第一,锁定能力差

Benefits of technology

第一,本发明通过将油酸修饰四氧化三铁磁性纳米颗粒与形状记忆聚氨酯复合,赋予微针温磁双响应特性。在一定的温度条件下,形状记忆聚氨酯由玻璃态转变为高弹态,同时在外部磁场作用下,磁性纳米颗粒产生驱动力,使微针由预设弯曲状态转变为直立状态,从而便于微针穿刺和植入。植入完成后,在人体生理温度作用下,形状记忆聚氨酯发生回复,使微针恢复至初始弯曲形态,并通过弯曲结构与周围组织形成机械嵌合作用,提高植入后的固定稳定性。该机制避免了传统直立微针主要依靠摩擦力固定导致的易迁移问题,为长期稳定的组织介入、局部递送和微型传感提供了新的技术方案。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122998591A_ABST
    Figure CN122998591A_ABST
Patent Text Reader

Abstract

The present application belongs to the technical field of microneedle, and particularly relates to a composite material microneedle and a preparation method and use thereof. The microneedle of the present application is integrally formed by a cylindrical section and a conical needle tip, the diameter of the cylindrical section is 100-200 μm, the height of the cylindrical section is 250-1500 μm, the height of the conical section is 50-600 μm, and the angle between the axis of the microneedle needle tip and the base plane is 10-55°. The microneedle is composed of OA@Fe3O4 (1-15 parts) and shape memory polyurethane (85-99 parts). The microneedle of the present application can realize overall continuous curvature deflection along the axial direction under the synergistic action of temperature-regulated shape memory effect and external magnetic field driving, and can adapt to various medical scenarios such as long-term drug delivery on high dynamic tissue surface, micro-sensor electrode, sutureless fixation, tissue engineering scaffold implantation, tumor target area positioning marker and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of microneedle technology, specifically relating to the application of a composite material microneedle. Background Technology

[0002] Microneedles, as a minimally invasive transdermal drug delivery and tissue intervention device, have been extensively studied in recent years in fields such as drug delivery, physiological signal monitoring, and minimally invasive surgery. Traditional microneedles are typically designed as upright, rigid structures, with the axis of the microneedle tip perpendicular to the base plane. They rely on the mechanical strength of the needle itself to penetrate tissue and are maintained in place by friction or surface adhesion. However, existing microneedles still have the following significant shortcomings in application: First, the locking ability is poor. Existing upright rigid microneedles have poor locking ability after implantation. In highly dynamic areas such as joints, the surface of the heart, and the peristaltic mucosa of the gastrointestinal tract, rigid microneedles are prone to relative displacement and loosening with the tissue, which can lead to drug delivery site deviation or sensor signal instability, and in severe cases, even cause mechanical damage to the tissue.

[0003] Second, if a flexible microneedle is used, uneven stress distribution can easily occur. Some reported flexible microneedles are made of flexible materials, but their bending deformation is often concentrated in local areas of the needle body (such as the tip or neck) rather than a uniform overall deflection. This localized stress concentration not only reduces the structural fatigue life of the microneedle but also easily leads to fracture during repeated deformation, increasing the risk of implantation.

[0004] Third, if a curved microneedle is attempted, existing technologies lack systematic optimization of geometric parameters. Current technologies lack quantitative analysis and orthogonal optimization of key parameters such as the microneedle shape, the aspect ratio of the cylindrical and conical segments, and the segment length ratio. This leads to a contradiction between the mechanical properties of the microneedle and the reliability of the fabrication process. For example, while a large aspect ratio is beneficial for deflection, it also increases the risk of needle breakage and tissue damage.

[0005] In summary, existing microneedle technology has significant shortcomings in high-dynamic environment anchoring, stable signal acquisition, minimally invasive anchoring, and tissue engineering fixation. There is an urgent need for a new microneedle structure that combines strong locking function, excellent mechanical properties, and good biocompatibility. Summary of the Invention

[0006] To address the problems of existing technologies, the present invention provides a... An application of a composite material microneedle, wherein the microneedle is curved in shape, and its shape and size parameters include: The microneedle consists of a cylindrical section and a conical section at the tip: the diameter of the cylindrical section is 100 μm to 200 μm; the height of the cylindrical section is 250 μm to 1500 μm; the height of the conical section is 50 μm to 600 μm; and the angle between the axis of the microneedle tip and the base plane is 10° to 55°. The purpose of the microneedles is to prepare biodegradable CT-detectable implantable micro-devices for tumor target localization.

[0007] Preferably, the optimal parameters of the microneedle are configured as follows: the diameter of the cylindrical section is 100 μm, the height of the cylindrical section is 750 μm, the height of the conical section is 150 μm, and the angle between the axis of the microneedle tip and the base plane is 30°.

[0008] Preferably, the microneedles are composed of the following components in parts by weight: 1-15 parts of oleic acid-modified iron oxide magnetic nanoparticles 85-99 parts of shape memory polyurethane material.

[0009] Preferably, the microneedles are composed of the following components in parts by weight: 3-13 parts of oleic acid-modified iron oxide magnetic nanoparticles 87-97 parts of shape memory polyurethane material.

[0010] Preferably, the shape memory polyurethane material is an amorphous polymer with a glass transition temperature of 37-45°C or a semi-crystalline polymer with a melting point of 37-45°C, and it is composed of diisocyanate, soft segment polymer, and... A linear polymer polymerized at a molar ratio of 1.2-8 : 1 : 0.2-7, with a molecular weight of 30,000-150,000; The soft segment polymer is polylactic acid, polyglycolic acid, polycaprolactone, polypolyol, or a copolymer of two or more of these.

[0011] Preferably, the shape memory polyurethane material has the structural formula shown in Formula I: Formula I Where x is selected from 1 to 10, and y is selected from 1 to 10; For the repeating unit of the soft segment polymer; It is a repeating unit of diisocyanate, or diisocyanate and The repeating unit of the copolymer.

[0012] Preferably, the soft segment polymer is a polymer of lactic acid and polyol; And / or, the structural formula of the soft segment polymer is shown in Formula II: Formula II Where m and n are independently selected from 4-50, and r is selected from 1-20; And / or, the diisocyanate is selected from aliphatic diisocyanates or aromatic diisocyanates, wherein the aliphatic diisocyanate is selected from hexamethylene diisocyanate, lysine diisocyanate, isophorone diisocyanate, dicyclohexylmethane diisocyanate, or a mixture of two or more thereof, and the aromatic diisocyanate is selected from toluene diisocyanate, diphenylmethane diisocyanate, or a mixture of two or more thereof.

[0013] The technical solution of the present invention achieves the following beneficial technical effects: First, this invention endows microneedles with thermo-magnetic dual-response properties by combining oleic acid-modified magnetite nanoparticles with shape memory polyurethane. Under certain temperature conditions, the shape memory polyurethane transforms from a glassy state to a highly elastic state. Simultaneously, under the influence of an external magnetic field, the magnetic nanoparticles generate a driving force, causing the microneedle to change from a preset bent state to an upright state, thus facilitating microneedle puncture and implantation. After implantation, under the influence of human physiological temperature, the shape memory polyurethane recovers, restoring the microneedle to its initial bent shape. The bent structure then forms a mechanical interlock with surrounding tissue, improving post-implantation fixation stability. This mechanism avoids the migration problems caused by traditional upright microneedles that rely primarily on friction for fixation, providing a new technical solution for long-term stable tissue intervention, local delivery, and micro-sensing.

[0014] Second, the composite geometry ensures uniform deformation and stress dispersion. This invention designs the microneedle as a combination of cylindrical and conical segments. Theoretical calculations and simulations have proven that the two segments exhibit good synchronization in deformation. The cylindrical segment, acting as an "equal stiffness carrier," provides a stable external force transmission path, effectively avoiding localized stress concentration. Orthogonal experiments show that the optimized microneedle exhibits uniform internal stress distribution at the maximum deflection angle, with no obvious stress concentration points or abnormal tip deformation, significantly improving the structural stability and implantation reliability during the microneedle morphology transformation process.

[0015] Third, the thermomagnetic dual-response mechanism enhances the flexibility and speed of regulation. This invention introduces magnetic nanoparticles, enabling the microneedle to be rapidly driven by a magnetic field, allowing for rapid, non-contact morphological adjustment under the influence of an external magnetic field. Simultaneously, the temperature response provides a reversible "shape-lock-and-recovery" cycle capability. This thermomagnetic dual-response mechanism achieves phased regulation of the morphological transformation process before and after microneedle implantation, improving the ease of operation and implantation stability, and providing a new technical solution for intelligent tissue intervention and local treatment.

[0016] Fourth, the systematic orthogonal experiments optimized the balance between the mechanical properties and fabrication reliability of the microneedles. This invention systematically investigated the effects of the cylindrical segment diameter, cylindrical segment height, and conical segment height on equivalent stress and strain through nine sets of orthogonal experiments. Range analysis clearly showed that the order of influence was cylindrical segment diameter > cylindrical segment height > conical segment height. Based on this, the initially optimized parameters were modified to reduce the aspect ratio to below 8, ensuring excellent overall deflection performance while avoiding the tissue damage risk associated with high aspect ratio needle breakage, thus achieving the optimal balance between mechanical properties and fabrication reliability.

[0017] Fifth, existing titanium clips exhibit artifacts under CT scans and are not biodegradable. In the preferred embodiment of this invention, microneedles are prepared using a composite material of oleic acid-modified magnetite nanoparticles and shape-memory polyurethane. These microneedles are clearly visible under CT scans, free of artifacts, and biodegradable, providing a potential biodegradable alternative to clinical titanium clips with lower imaging artifacts.

[0018] In summary, this invention overcomes multiple technical challenges of traditional microneedles, such as easy detachment in high-dynamic environments, susceptibility to motion artifacts in signal acquisition, lack of active anchoring mechanisms, and reliance on chemical adhesives or sutures for tissue engineering scaffold fixation, through optimized design of microneedle composite geometry and introduction of thermomagnetic response shape memory materials.

[0019] Obviously, based on the above description of the present invention, and according to common technical knowledge and conventional methods in the field, various other modifications, substitutions or alterations can be made without departing from the basic technical concept of the present invention.

[0020] The following detailed embodiments further illustrate the above-described content of the present invention. However, this should not be construed as limiting the scope of the present invention to the following examples. All technologies implemented based on the above-described content of the present invention fall within the scope of the present invention. Attached Figure Description

[0021] Figure 1 CT images of rats after surgery; Figure 2The figures represent the simulation results of the total deformation of the microneedle structure in each group of orthogonal experiments; where a is the simulation result of the overall deflection deformation of the microneedle in the thermomagnetic response of parameter combination ①, b is the simulation result of the overall deflection deformation of the microneedle in the thermomagnetic response of parameter combination ②, c is the simulation result of the overall deflection deformation of the microneedle in the thermomagnetic response of parameter combination ③, d is the simulation result of the overall deflection deformation of the microneedle in the thermomagnetic response of parameter combination ④, e is the simulation result of the overall deflection deformation of the microneedle in the thermomagnetic response of parameter combination ⑤, f is the simulation result of the overall deflection deformation of the microneedle in the thermomagnetic response of parameter combination ⑥, g is the simulation result of the overall deflection deformation of the microneedle in the thermomagnetic response of parameter combination ⑦, h is the simulation result of the overall deflection deformation of the microneedle in the thermomagnetic response of parameter combination ⑧, and i is the simulation result of the overall deflection deformation of the microneedle in the thermomagnetic response of parameter combination ⑨.

[0022] Figure 3 The figures represent the simulation results of the equivalent elastic strain of the microneedle structure in each group of orthogonal experiments. Specifically, a represents the simulation result of the equivalent elastic strain of the microneedle with overall thermomagnetic response deflection in parameter combination ①, b represents the simulation result of the equivalent elastic strain of the microneedle with overall thermomagnetic response deflection in parameter combination ②, c represents the simulation result of the equivalent elastic strain of the microneedle with overall thermomagnetic response deflection in parameter combination ③, d represents the simulation result of the equivalent elastic strain of the microneedle with overall thermomagnetic response deflection in parameter combination ④, e represents the simulation result of the equivalent elastic strain of the microneedle with overall thermomagnetic response deflection in parameter combination ⑤, f represents the simulation result of the equivalent elastic strain of the microneedle with overall thermomagnetic response deflection in parameter combination ⑥, g represents the simulation result of the equivalent elastic strain of the microneedle with overall thermomagnetic response deflection in parameter combination ⑦, h represents the simulation result of the equivalent elastic strain of the microneedle with overall thermomagnetic response deflection in parameter combination ⑧, and i represents the simulation result of the equivalent elastic strain of the microneedle with overall thermomagnetic response deflection in parameter combination ⑨.

[0023] Figure 4 The figures represent the simulation results of the equivalent elastic stress of the microneedle structure in each group of orthogonal experiments. Specifically, a represents the simulation result of the equivalent elastic stress of the microneedle with overall temperature and magnetic response deflection in parameter combination ①; b represents the simulation result of the equivalent elastic stress of the microneedle with overall temperature and magnetic response deflection in parameter combination ②; c represents the simulation result of the equivalent elastic stress of the microneedle with overall temperature and magnetic response deflection in parameter combination ③; d represents the simulation result of the equivalent elastic stress of the microneedle with overall temperature and magnetic response deflection in parameter combination ④; e represents the simulation result of the equivalent elastic stress of the microneedle with overall temperature and magnetic response deflection in parameter combination ⑤; f represents the simulation result of the equivalent elastic stress of the microneedle with overall temperature and magnetic response deflection in parameter combination ⑥; g represents the simulation result of the equivalent elastic stress of the microneedle with overall temperature and magnetic response deflection in parameter combination ⑦; h represents the simulation result of the equivalent elastic stress of the microneedle with overall temperature and magnetic response deflection in parameter combination ⑧; and i represents the simulation result of the equivalent elastic stress of the microneedle with overall temperature and magnetic response deflection in parameter combination ⑨.

[0024] Figure 5The simulation results are for the conical microneedle structure; where a is the deformation simulation result of the conical microneedle, b is the equivalent elastic strain simulation result of the conical microneedle, and c is the equivalent elastic stress simulation result of the conical microneedle.

[0025] Figure 6 The simulation results are for the microneedles selected in Comparative Example 2.

[0026] Figure 7 The simulation results are for the microneedles selected in Comparative Example 3.

[0027] Figure 8 The simulation results are for the microneedles selected in Comparative Example 4.

[0028] Figure 9 The apparent morphology and magnetic adsorption properties of ISO2-PU and OA@Fe3O4 / ISO2-PU composite materials are shown, where a represents the apparent morphology and b represents the magnetic adsorption properties.

[0029] Figure 10 The images show the infrared spectra of OA@Fe3O4, ISO2-PU, and OA@Fe3O4 / ISO2-PU composites, where a is the full spectrum and bd are magnified views of the corresponding regions.

[0030] Figure 11 Peak fitting for the stretching vibration region of ISO2-PU and its composite material -CO is given, where a is the peak fitting for the sample with 0% OA@Fe3O4 addition, b is the peak fitting for the sample with 1% OA@Fe3O4 addition, c is the peak fitting for the sample with 3% OA@Fe3O4 addition, d is the peak fitting for the sample with 5% OA@Fe3O4 addition, e is the peak fitting for the sample with 8% OA@Fe3O4 addition, f is the peak fitting for the sample with 10% OA@Fe3O4 addition, g is the peak fitting for the sample with 13% OA@Fe3O4 addition, and h is the peak fitting for the sample with 15% OA@Fe3O4 addition.

[0031] Figure 12 This is the hysteresis loop (MH curve) of the composite material.

[0032] Figure 13 The results are from compressive stress-strain experiments on composite materials.

[0033] Figure 14 The figures show the characterization and schematic diagram of the microneedles, where a is the schematic diagram of the master mold design, b is the prototype sample, cd is the optical morphology of the microneedle array under a stereomicroscope, and ef is the microneedle structure characterization under SEM.

[0034] Figure 15The process of thermomagnetic deflection and recovery of the microneedle is shown in the figure. In the figure, a represents the overall deflection of the thermomagnetic response microneedle in the initial state of bending, b represents the overall deflection of the thermomagnetic response microneedle in the state of straightening after heating and applying a magnetic field, and c represents the overall deflection of the thermomagnetic response microneedle in the state of bending after heating.

[0035] Figure 16 The safety characteristics of microneedles are shown in Figure 1, where a represents the hemolysis rate test result, b represents the CCK-8 assay result, and c represents the live / dead L929 cell test result. Detailed Implementation

[0036] It should be noted that the algorithms for data acquisition, transmission, storage and processing steps not specifically described in the embodiments, as well as the hardware structures and circuit connections not specifically described, can all be implemented using content already disclosed in the prior art.

[0037] Example 1: Application of a composite material microneedle The composite material microneedles of this embodiment are made of thermo-magnetic responsive composite material, which is composed of the following components in parts by weight: 1-15 parts of oleic acid-modified iron oxide magnetic nanoparticles 85-99 parts of shape memory polyurethane material.

[0038] In this embodiment, the oleic acid-modified magnetite nanoparticles (OA@Fe3O4) were purchased from Jiangsu Zhichuan Technology, 10 nm in size.

[0039] The shape memory polyurethane material can optionally be a polyurethane material with shape memory function. As a preferred example, the shape memory polyurethane material of this embodiment is prepared with reference to Chinese Patent CN114634608B, specifically ISO2-PU.

[0040] The composite material microneedles in this embodiment were prepared according to the following method: A 25 mg / mL OA@Fe3O4 dichloromethane dispersion was added dropwise to a 10 wt.% ISO2-PU trichloromethane solution, resulting in OA@Fe3O4 addition amounts of 0%, 1%, 3%, 5%, 8%, 10%, 13%, and 15% (OA@Fe3O4 / PU, w / w). After mechanical stirring, the mixture was transferred to a polytetrafluoroethylene mold. After solvent evaporation at room temperature for 24 h, the mixture was transferred to a vacuum drying oven and vacuum dried (37 °C) until the mass was constant, in order to prepare OA@Fe3O4 / ISO2-PU composite materials with different magnetic nanoparticle concentrations.

[0041] Oleic acid-modified magnetite nanoparticles / ISO2-PU composite microneedles were prepared by hot pressing using a flat vulcanizing machine. The hot pressing process parameters were optimized based on rheological test results: the temperatures of the upper and lower chamber plates of the flat vulcanizing machine were set to 150 ℃ and 110 ℃, respectively. First, the prepared OA@Fe3O4 / ISO2-PU composite material was pre-pressed into a 1.5×1.5×0.5 mm square preform. This preform was then placed in the center of the microneedle mold cavity and preheated for 3 min to fully soften the composite material. A constant pressure was applied until the mold cavity was completely filled, and the pressure was held for 3 min. After the mold cooled naturally to room temperature, the microneedles were demolded, yielding the shape memory composite microneedles in their initial bent state.

[0042] The shape memory composite microneedles, initially bent and obtained after demolding, were placed on a precision thermostat and heated to 60 °C for 3 min. At this point, the polymer molecular chain segments gained sufficient thermal energy, and the material transitioned from a glassy state to a highly elastic state. The storage modulus decreased significantly, and the material exhibited excellent deformation capabilities, laying the foundation for subsequent magnetically driven shape control.

[0043] An N52 neodymium iron boron (NdFeB) permanent magnet was used as the external gradient magnetic field source and placed at a predetermined distance directly below the microneedle. The microneedle, in a highly elastic state, underwent orientation deflection along the magnetic field direction due to the magnetic driving force generated by the magnetic field gradient on its internal magnetic nanoparticles, transforming from an initial "bent state" to a temporary "upright state." While maintaining the external magnetic field constraint, the heat source of the isothermal stage was cut off, and the sample was rapidly cooled to 20 °C and held for 2 min. This froze the conformation of the polymer molecular chain segments, thus fixing the temporary upright shape of the microneedle. After the external magnetic field was removed, the microneedle stably maintained its upright state.

[0044] When microneedles fixed in an upright state are placed in a constant temperature environment of 37 °C, the polymer molecular chain segments are reactivated, and the microneedles spontaneously recover to their initial bent state through entropic elastic recovery. The entire shape recovery process of the microneedles is recorded in real time using an optical microscope, and the bending angle of the microneedles at different time points is quantitatively measured to calculate the shape recovery rate and shape recovery time.

[0045] The bending performance of the microneedles is verified through simulation experiments. In the finite element simulation process of this invention, Ansys Workbench was used for simulation analysis. The entire simulation optimization and parameterization process strictly followed the logical unfolding of geometric structure import, material parameter setting, coordinate system and mesh generation, boundary condition application (fixed support and moment loading), and solution analysis to ensure the reliability of the simulation results. The microneedle material was modeled using shape memory polyurethane (ISO2-PU) as the matrix. The simulation parameters are as follows: Young's modulus was set to 3588.55 MPa at 25 ℃ and 1023.10 MPa at 37 ℃; Poisson's ratio was set to 0.48; bulk modulus was set to 8525 MPa; shear modulus was set to 345.61 MPa; ultimate compressive strength was set to 53 MPa; and ultimate tensile strength was set to 30 MPa.

[0046] Considering that the main role of OA@Fe3O4 in the composite system is to provide magnetic response driving force, its influence on the overall mechanical properties is mainly manifested in the increase of equivalent density and the correction of elastic modulus caused by volume fraction. Therefore, the equivalent homogenization method is used to treat the composite material system in the simulation.

[0047] Specifically, by introducing an equivalent density correction term corresponding to the volume fraction of magnetic particles and an elastic modulus correction coefficient, the OA@Fe3O4 / ISO2-PU composite material is equivalent to a uniform and continuous shape memory polyurethane material model.

[0048] The overall deflection behavior of microneedles is mainly dominated by the macroscopic elastic recovery capability of shape memory polymers, while magnetic nanoparticles only provide driving torque under external magnetic field and do not change the dominant deformation mechanism of the material. Therefore, the simulation results can effectively reflect the overall mechanical response trend of actual composite microneedles.

[0049] The microneedle parameters are as follows: cylindrical segment diameter 100 μm, cylindrical segment height 600 μm, tip conical segment height 150 μm, center-to-center spacing between adjacent microneedles within the array 400 μm, initial axis of the microneedle tip angle with the substrate plane designed to be 30°, and the designed microneedle patch size 1.5 × 1.5 × 0.5 mm. The upright microneedle mold is identical to the curved microneedle mold in all structural parameters except that the axis of the microneedle tip is perpendicular to the substrate plane.

[0050] Simulation results show that the composite geometric microneedle can achieve uniform deflection (with controllable deflection angle) under magnetic field gradient or temperature excitation. Furthermore, at the maximum deflection angle, the internal stress distribution of the microneedle structure is uniform, and no obvious stress concentration points or abnormal tip deformation were found.

[0051] Based on the aforementioned composite material microneedles, this embodiment provides a novel application for composite material microneedles. In this embodiment, a mammary gland microneedle implantation model was established using female SD rats (180 ± 20 g). The experimental animals were acclimatized for one week before the surgical procedure. Preoperatively, the rats were anesthetized using an appropriate anesthesia method, the hair in the mammary gland area was shaved, and the skin was disinfected sequentially. The animals were fixed supine on a sterile operating table, fully exposing the ventral mammary gland area. A longitudinal incision of approximately 3 cm was made approximately 1.5 cm lateral to the nipple along the mammary gland area. The skin and subcutaneous tissue were dissected layer by layer to expose the mammary gland tissue, and an implantation site was established within the mammary gland using blunt dissection.

[0052] A commonly used titanium clip positioning marker was implanted at the left breast implantation site as a control. At the right breast implantation site, the prepared composite microneedles (a sample with 15% OA@Fe3O4 / PU) were vertically inserted into the breast tissue, ensuring the microneedles were fully inserted into the target area. After implantation, the microneedles exhibited shape memory recovery behavior under the influence of body temperature, returning from an upright state to a pre-set curved state, thus stabilizing the microneedles with the surrounding tissue and improving the fixation stability after implantation.

[0053] After implantation, the surgical incision was sutured, and the animal's vital signs, activity level, and wound healing were observed during the postoperative recovery period. Micro-CT imaging was used postoperatively to evaluate the imaging effect, spatial localization ability, CT imaging, and artifact generation after microneedle implantation.

[0054] Rats were continuously monitored, and CT images were recorded on days 1, 7, 11, 29, and 50. Figure 1 As shown (the left side is the titanium clip, and the right side is the microneedle), the microneedles of this invention achieve good self-fixation in vivo, with no obvious displacement. The microneedles of this invention exhibit excellent imaging performance, clear spatial positioning, and minimal artifact interference, meeting the requirements for long-term tracking. By day 50, the microneedles had begun to gradually degrade and be safely metabolized in vivo.

[0055] Composite material microneedles utilize the shape memory effect to achieve precise active anchoring in cavity tissues through a mechanism of "straight needle insertion and bending upon heating," effectively avoiding the clinical pain points of traditional titanium clips, such as foreign body retention, artifacts, and positional migration. At the same time, combined with its biodegradable biocompatible material and radiopaque tracer function, these microneedles not only provide clear, artifact-free postoperative imaging localization but also can be metabolized and absorbed over time after completing the treatment, providing patients with a minimally invasive, precise, and long-term foreign body-free intelligent localization solution.

[0056] Example 2: Application of composite material microneedles in intelligent transdermal / intra-tissue drug delivery patches under dynamic physiological conditions A microneedle patch is constructed based on the composite material microneedles described in Example 1. The microneedle patch has dimensions of 1.5 × 1.5 × 0.5 mm, and the center-to-center distance between adjacent microneedles within the patch is 400 μm. The cylindrical segment has a diameter of 100 μm and a height of 600 μm, the conical segment has a height of 150 μm, and the angle between the axis of the microneedle tip and the substrate plane is 30°.

[0057] This microneedle patch is used for long-term drug delivery in highly dynamic areas such as joints, the surface of the heart, or the peristaltic mucosa of the gastrointestinal tract. During use, the microneedle patch is first placed in a constant temperature environment of 60 °C. Under an external magnetic field, the microneedles are transformed from an initial bent state to an upright state. The patch is then attached to the target tissue surface, and slight pressure is applied to allow the upright microneedles to vertically penetrate the tissue surface. After attachment, the external heat source is removed, allowing the microneedle patch to gradually return to its initial bent state under the influence of tissue temperature (37 °C). The microneedle tips undergo overall deflection within the tissue, forming a three-dimensional physical anchoring structure.

[0058] Example 3: Application of composite material microneedles in flexible bioelectrodes and deep signal monitoring The composite material microneedles prepared in Example 1 were used to electrically connect the microneedle array to a flexible circuit board to form a flexible bioelectrode patch.

[0059] This electrode patch was used for monitoring electromyographic (EMG) signals in humans. During use, the microneedle was inserted into the stratum corneum of the skin in an upright position as described in Example 2. After the microneedle returned to a bent state at tissue temperature, the microneedle tip was stably anchored in the dermis, and a stable contact was formed between the electrode and the tissue interface. EMG signals were recorded in two modes: continuous grip force output (5 kg, 120 s) and dynamic grip force variation (2–8 kg cycles, 0.2 Hz).

[0060] The results show that, in static grip force output mode, the signal-to-noise ratio (SNR) of the electrode of this invention is 28.6 dB, which is not significantly different from that of the traditional upright microneedle electrode (29.1 dB). In dynamic grip force variation mode, the SNR of the electrode of this invention remains at 27.4 dB, and the signal amplitude fluctuation coefficient (CV) is 6.3%, while the SNR of the traditional upright microneedle electrode drops to 18.2 dB, and the CV is as high as 24.7%. These results indicate that the microneedle of this invention can deflect with the overall tissue during skin stretching, and the contact impedance at the electrode-tissue interface remains stable (impedance change <5%), effectively suppressing motion artifacts.

[0061] This electrode is also suitable for continuous monitoring of electroencephalography (implanted in the dermis of the scalp) and interstitial fluid biochemical indicators (such as glucose and lactate).

[0062] Example 4: Application of composite microneedles as tissue adhesion and mechanical anchors in minimally invasive surgery The composite microneedles prepared in Example 1 were installed on the end effector of a minimally invasive surgical instrument and used as micro-anchors.

[0063] In minimally invasive interventional surgery, this microneedle can act as a "miniature anchor." In an upright position, it is easily inserted into narrow lumens or interstitial spaces. Once it reaches the target site, it deflects entirely through a temperature-controlled response, instantly forming a reliable mechanical connection. This avoids the concentrated stress damage to delicate tissues (such as blood vessels and nerves) caused by traditional sutures, achieving a uniform distribution of stress within the tissue.

[0064] In addition, the microneedle can also be used as a fixation component for soft tissue repair scaffolds, to fix decellularized dermal matrix or artificial blood vessels to the defect site, and as an end-grabbing mechanism in microsurgical instruments to achieve non-destructive manipulation of small tissue flaps.

[0065] Example 5: Application of composite microneedles as bioscaffold fixation components in tissue engineering and regenerative medicine The composite material microneedles prepared in Example 1 are used to fix the scaffold to the surface of the host tissue during the implantation of artificial skin, artificial cartilage, or tissue engineering scaffolds.

[0066] Utilizing the overall deflection force generated during the shape memory recovery process of the microneedles, they can grasp host tissue like "miniature plant roots," thus assisting biological integration through physical means. This method eliminates the need for chemical adhesives, reduces the risk of cytotoxicity, and provides a stable mechanical environment for the growth of new tissue.

[0067] Example 6: Parameter combination of a composite material microneedle ① The microneedle parameters are as follows: cylindrical segment diameter 100 μm, cylindrical segment height 250 μm, conical segment height 50 μm, and other parameters are consistent with those described in Example 1. Based on the simulation analysis described in Example 1, a simulation experiment was conducted on this microneedle, and the simulation results are as follows: Figure 2 As shown in figures a, 3a, and 4a. Figure 2a shows the total deformation test result, figure 3a shows the equivalent elastic strain test result, and figure 4a shows the equivalent stress test result.

[0068] Example 7: Parameter combination of a composite material microneedle ② The microneedle parameters are as follows: cylindrical segment diameter is 100 μm, cylindrical segment height is 500 μm, conical segment height is 200 μm, and other parameters are consistent with those described in Example 1. Based on the simulation analysis described in Example 1, a simulation experiment was conducted on this microneedle, and the simulation results are as follows. Figure 2 Figures 2b, 3b, and 4b are shown. Figure 2b shows the total deformation test result, Figure 3b shows the equivalent elastic strain test result, and Figure 4b shows the equivalent stress test result.

[0069] Example 8: Parameter combination of a composite material microneedle ③ The composite material microneedles prepared in Example 2 were used. The microneedles had the following parameters: a cylindrical segment diameter of 100 μm, a cylindrical segment height of 750 μm, and a conical segment height of 450 μm. The remaining parameters were consistent with those described in Example 1. Based on the simulation analysis described in Example 1, a simulation experiment was conducted on these microneedles. The simulation results are as follows: Figure 2 Figures c, 3c, and 4c are shown. Figure 2c shows the total deformation test result, Figure 3c shows the equivalent elastic strain test result, and Figure 4c shows the equivalent stress test result.

[0070] Example 9: Parameter combination of a composite material microneedle ④ The microneedle parameters are as follows: cylindrical segment diameter 150 μm, cylindrical segment height 375 μm, conical segment height 150 μm, and other parameters are consistent with those described in Example 1. Based on the simulation analysis described in Example 1, a simulation experiment was conducted on this microneedle, and the simulation results are as follows: Figure 2 The results are shown in d, 3d, and 4d. 2d represents the total deformation test result, 3d represents the equivalent elastic strain test result, and 4d represents the equivalent stress test result.

[0071] Example 10: Parameter combination of a composite material microneedle (⑤) The microneedle parameters are as follows: cylindrical segment diameter 150 μm, cylindrical segment height 750 μm, conical segment height 450 μm, and other parameters are consistent with those described in Example 1. Based on the simulation analysis described in Example 1, a simulation experiment was conducted on this microneedle, and the simulation results are as follows: Figure 2 The results are shown in e, 3e, and 4e. 2e represents the total deformation experimental result, 3e represents the equivalent elastic strain experimental result, and 4e represents the equivalent stress experimental result.

[0072] Example 11 Parameter combination of a composite material microneedle ⑥ The microneedle parameters are as follows: cylindrical segment diameter 150 μm, cylindrical segment height 1125 μm, conical segment height 225 μm, and other parameters are consistent with those described in Example 1. Based on the simulation analysis described in Example 1, a simulation experiment was conducted on this microneedle, and the simulation results are as follows: Figure 2 The results are shown in f, 3f, and 4f. 2f represents the total deformation test result, 3f represents the equivalent elastic strain test result, and 4f represents the equivalent stress test result.

[0073] Example 12: Parameter combination of a composite material microneedle ⑦ The microneedle parameters are as follows: cylindrical segment diameter 200 μm, cylindrical segment height 500 μm, conical segment height 300 μm, and other parameters are consistent with those described in Example 1. Based on the simulation analysis described in Example 1, a simulation experiment was conducted on this microneedle, and the simulation results are as follows: Figure 2 The values ​​g, 3g, and 4g are shown. 2g represents the total deformation experimental result, 3g represents the equivalent elastic strain experimental result, and 4g represents the equivalent stress experimental result.

[0074] Example 13: Parameter combination of a composite material microneedle (⑧) The microneedle parameters are as follows: cylindrical segment diameter 200 μm, cylindrical segment height 1000 μm, conical segment height 200 μm, and other parameters are consistent with those described in Example 1. Based on the simulation analysis described in Example 1, a simulation experiment was conducted on this microneedle, and the simulation results are as follows: Figure 2 The results are shown in h, 3h, and 4h. 2h represents the total deformation test result, 3h represents the equivalent elastic strain test result, and 4h represents the equivalent stress test result.

[0075] Example 14: Parameter combination of a composite material microneedle ⑨ The microneedle parameters are as follows: cylindrical segment diameter 200 μm, cylindrical segment height 1500 μm, conical segment height 600 μm, and other parameters are consistent with those described in Example 1. Based on the simulation analysis described in Example 1, a simulation experiment was conducted on this microneedle, and the simulation results are as follows: Figure 2 The results are shown in i, 3i, and 4i. 2i represents the total deformation test result, 3i represents the equivalent elastic strain test result, and 4i represents the equivalent stress test result.

[0076] Example 15 Qualitative Analysis of Microneedle Deflection Taking the parameters in Table 1 as an example, the overall deflection performance and stress concentration of the microneedle are analyzed.

[0077] Table 1 Conical segment rotation angle : Moment of inertia in, This is the distance from the tip of the conical segment. D 2 is the diameter of the base. L 2 represents the height of the conical segment; Bending moment in, q For a uniformly distributed load (external force per unit length); Angle integral in, EThe elastic modulus of the material; Substituting the parameters yields .

[0078] Cylindrical segment corner : The cylindrical segment has a uniform cross-section, and the moment of inertia is... in, L 1 represents the height of the cylindrical segment; Substituting, we get Bending moment Angle integral in, L The total length is the sum of the cylindrical and conical segments; Substituting the parameters, we get Total turning angle, ; The difference in contribution between the two corners: 14.2%.

[0079] Based on the above analysis, the cylindrical segment of the microneedle in this embodiment has a constant moment of inertia and uniform stiffness, providing an "equal stiffness carrier" for external force transmission; the angular contribution ratios of the conical segment and the cylindrical segment are 43% and 57% respectively, with a difference of 14% (<30%), indicating good deformation synchronization. Therefore, designing the microneedle as an integrated design of the cylindrical and conical segments can achieve stable overall deflection of the microneedle, uniform stress distribution, and reduce the risk of microneedle breakage.

[0080] Comparative Example 1 A simulation experiment was conducted on a conical microneedle with a base diameter of 150 μm and a height of 450 μm, based on the simulation analysis described in Example 1. The experimental results are as follows: Figure 5 As shown.

[0081] It can be seen that the tip of the cone is extremely easy to deform, while the middle and lower parts have extremely high stiffness. The contribution of the rotation angle is concentrated at the tip, and the total contribution of the middle and lower parts to the rotation angle is less than 25%, which is insufficient to achieve overall deflection.

[0082] Comparative Example 2 The composite material microneedles prepared in Example 1 were used. The microneedle parameters were as follows: cylindrical segment diameter of 100 μm, cylindrical segment height of 680 μm, conical segment height of 102 μm, and the angle between the microneedle axis and the substrate plane of 60°. Other parameters were consistent with those described in Example 1. Based on the simulation analysis described in Example 1, a simulation experiment was conducted on this microneedle. The simulation results are as follows: Figure 6 As shown.

[0083] Experimental results show that the microneedles under these parameter settings cannot return to an upright state.

[0084] Comparative Example 3 The composite microneedles prepared in Example 1 were used. The microneedles had the following parameters: a cylindrical segment diameter of 300 μm, a cylindrical segment height of 1500 μm, a conical segment height of 600 μm, and an angle of 30° between the microneedle axis and the substrate plane. All other parameters were consistent with those described in Example 1. Based on the simulation analysis described in Example 1, a simulation experiment was conducted on this microneedle. The simulation results are as follows: Figure 7 As shown.

[0085] Experimental results show that the microneedles under these parameter settings cannot return to an upright state.

[0086] Comparative Example 4 The composite material microneedles prepared in Example 1 were used. The microneedle parameters were as follows: cylindrical segment diameter of 250 μm, cylindrical segment height of 1500 μm, conical segment height of 375 μm, and the angle between the microneedle axis and the substrate plane of 15°. Other parameters were consistent with those described in Example 1. Based on the simulation analysis described in Example 1, a simulation experiment was conducted on this microneedle. The simulation results are as follows: Figure 8 As shown.

[0087] Experimental results show that the microneedles under these parameter settings cannot return to an upright state.

[0088] Based on the simulation results of Examples 6-14 and the comparative examples, it can be seen that the cylindrical segment diameter is 100 μm to 200 μm; the cylindrical segment height is 250 μm to 1500 μm; the conical segment height is 50 μm to 600 μm; and the angle between the microneedle axis and the substrate plane is 30°. Microneedles within these parameter ranges can all achieve bending. Furthermore, bending can also be achieved within the angle range of 10° to 55° between the microneedle axis and the substrate plane. However, outside these parameter ranges, or with changes in the microneedle shape (conical shape), a good bending effect cannot be achieved.

[0089] In particular, when (L1+L2) / D2=9>8, it exceeds the maximum ratio for preparing microneedles, making them prone to breakage and posing a risk of mechanical damage to tissues. Therefore, when designing microneedle parameters, the microneedle parameters L1, L2 and D2 are optimized, and (L1+L2) / D2 is controlled within 8.

[0090] The technical solution of the present invention will be further illustrated by the following experiments. The OA@Fe3O4 / ISO2-PU composite material used in the following experiments was prepared according to the method of Example 1; the shape memory microneedles in the initial bending state were prepared according to the method of Example 1, and the material used to prepare the microneedles was OA@Fe3O4 / ISO2-PU composite material with an addition amount of 15% OA@Fe3O4.

[0091] Example 1: Characterization of thermomagnetic response composite materials I. Experimental Methods 1. Infrared characterization The hot-pressed thin film samples were measured using a transmission mode Fourier transform infrared spectrometer, with a scanning range of 400-4000 cm⁻. 1 4 cm⁻ 1 A total of 16 scans were performed to acquire FT-IR spectra.

[0092] 2. Saturation magnetization The static magnetic behavior of the sample at room temperature was tested using a vibrating sample magnetometer with a magnetic field range of -20000 to 2000 Oe. The change in the sample magnetization intensity with the applied magnetic field H was measured.

[0093] 3. Compression mechanical properties The sample was hot-pressed into a cylindrical specimen with a bottom diameter of 8 mm and a height of 4 mm using a mold, and the loading rate for the compression test was 5.0 mm / min.

[0094] II. Experimental Results 1. Surface morphology of OA@Fe3O4 / ISO2-PU composite material Example 1 prepared OA@Fe3O4 / ISO2-PU composite materials with different OA@Fe3O4 contents. Figure 9 As can be seen, pure ISO2-PU is light yellow and transparent. With the increase of OA@Fe3O4 content, the color of the composite material gradually changes from light brown to dark black. This is attributed to the high light absorption capacity of Fe3O4 nanoparticles. The increase in its content leads to a decrease in the overall light transmittance of the composite material. Moreover, the color distribution of each group is uniform, and no obvious particle agglomeration or color spot phenomenon was observed, indicating that OA@Fe3O4 nanoparticles can be macroscopically and uniformly dispersed in the polyurethane matrix.

[0095] Figure 9 b further demonstrates the magnetic adsorption behavior of each composite material group. Pure ISO2-PU did not show obvious magnetic adsorption, but after the introduction of OA@Fe3O4, all composite materials could be adsorbed by a permanent magnet (20*10*5 mm) and stably attached to the magnet surface, indicating that the composite materials have magnetic response properties, laying the foundation for subsequent thermo-magnetic response shape memory behavior.

[0096] 2. Infrared spectrum of OA@Fe3O4 / ISO2-PU composite material In polymer nanocomposite systems, the interfacial interaction between inorganic functional fillers and the polymer matrix is ​​a key factor determining the overall performance of the material. This experimental example uses FTIR to characterize the interaction between OA@Fe3O4 nanoparticles and the ISO2-PU matrix.

[0097] like Figure 10 As shown in Figure a, the infrared spectrum of the pure ISO2-PU matrix exhibits typical polyurethane structural characteristics (Table 2). 3300~3400 cm⁻¹ -1 A relatively broad absorption band appears within this range, mainly attributed to the stretching vibration of NH in the urethane group; ~3000 cm⁻¹ -1 The nearby absorption peaks represent the stretching vibrations of the -CH2 and -CH3 groups in the soft and hard segments of the polyurethane; ~1750 cm⁻¹ -1 The absorption peak at 1731–1600 cm⁻¹ mainly originates from the stretching vibration of the carbonyl group in the soft segment of the ester; -1 and ~1530 cm -1 The absorption peak at 1100–1130 cm⁻¹ corresponds to the characteristic peaks of amide I (C=O group) and amide II (NH group); -1 The absorption peaks in the vicinity are mainly attributed to the asymmetric stretching vibrations of the COC bonds in the soft segment.

[0098] OA@Fe3O4 at ~2900 and ~2850 cm⁻¹ -1 Nearby, asymmetric and symmetric stretching vibration peaks appeared in the CH2 group of the long alkyl chain of oleic acid, and simultaneously at 1580–1600 cm⁻¹. -1 and 1400~1420 cm -1 Antisymmetric and symmetric stretching vibration peaks of the carboxylate group were observed at 560–580 cm⁻¹. -1 The characteristic absorption peaks appearing within the range are attributed to the stretching vibrations of the Fe-O bond.

[0099] After introducing OA@Fe3O4 into ISO2-PU, the composite materials in each group retained the characteristic absorption peaks of ISO2-PU, and no obvious new absorption peaks appeared. With increasing OA@Fe3O4 content, the 560~580 cm⁻¹ peaks... -1 The characteristic absorption peaks of Fe-O at the location gradually become more obvious. Figure 10 c) indicates that the magnetic nanoparticles have been successfully introduced into the polyurethane matrix. Simultaneously, a certain degree of wavenumber redshift is observed, indicating a change in the local chemical environment of the Fe3O4 surface. This can be attributed to hydrogen bonding between the urethane groups of ISO2-PU and the active groups on the OA@Fe3O4 surface (the hydroxyl groups on the Fe3O4 surface can act as hydrogen bond acceptors or donors, interacting with -NH and C=O groups in the polyurethane). 2800~3000 cm⁻¹ -1 The changes in the intensity and shape of the absorption peaks within the range are mainly due to the interweaving of the stretching vibrations of the -CH2 and -CH3 groups in the ISO2-PU and oleic acid coating layers. The 1100–1300 cm⁻¹ range... -1The position of the COC absorption peak within the range did not change significantly, indicating that the addition of nanoparticles did not have a significant impact on the basic chemical structure of the ISO2-PU soft segment.

[0100] Table 2. Assignment of infrared absorption peaks for OA@Fe3O4, ISO2-PU, and OA@Fe3O4 / ISO2-PU In ISO2-PU, the -NH group in the carbamate group is the main hydrogen bond donor, and the carbonyl group (amide carbonyl in the hard segment and ester carbonyl in the soft segment) is the main hydrogen bond acceptor. The spatial topological association between the two forms a stable polymeric physical cross-linking network. When Fe3O4 nanoparticles with oleic acid groups modified on the surface are introduced, the carboxyl group (-COO) of oleic acid on the particle surface participates as a novel hydrogen bond acceptor, influencing the hydrogen bond network of the matrix.

[0101] Hydrogen bond donor 3300~3500 cm -1 The spectral signal in the region is quite complex, including stretching vibrations of the polyurethane matrix -NH, stretching vibrations of hydroxyl groups on the particle surface and trace amounts of adsorbed water molecules OH, and significant overlap between different absorption peaks. Figure 10 d). The absorption peaks in this region fluctuate significantly, making it difficult to accurately distinguish between free -NH and hydrogen-bonded -NH using peak fitting. Therefore, the peak shape variations in this region are only used as a qualitative indicator of the interfacial interaction between OA@Fe3O4 and ISO2-PU, and are not used for quantitative peak separation.

[0102] Hydrogen bond acceptor 1650~1800 cm -1 The C=O stretching vibration region within this range has a well-defined boundary and clear chemical classification. Peak separation was performed in this region to further analyze the hydrogen bonding state in the composite material. Gaussian fitting was performed on this region using Peakfit software. The results are as follows: Figure 11 As shown, depending on the microenvironment in which the carbonyl group is located, the carbonyl component in the low wavenumber direction is usually affected by intermolecular hydrogen bonds, while the component in the high wavenumber direction corresponds to the free carbonyl environment.

[0103] Further semi-quantitative analysis was performed on the area ratio of hydrogen-bonded carbonyl groups to free carbonyl groups to characterize the degree of carbonyl hydrogen bond association (Table 3). The results showed that the low wavenumber C=O component peak area accounted for 60.77% in the pure ISO2-PU sample. This proportion gradually decreased with the addition of nanoparticles, dropping to 53.03% at an 8% addition level. Further increases in nanoparticle content led to a partial recovery of this proportion, with values ​​of 57.70%, 55.81%, and 59.58% for the 10%, 13%, and 15% samples, respectively.

[0104] Table 3 Peak fitting of the stretching vibration region of ISO2-PU and its composite material-CO The above results indicate that the introduction of OA@Fe3O4 nanoparticles altered the local microenvironment of the carbonyl groups. At low and medium concentrations, the oleic acid modification layer affected the PU segment arrangement, causing some carbonyl groups to become relatively free. When the concentration was further increased to 10-15%, partial aggregation may occur between particles, enhancing the interaction between nanoparticles and increasing the non-uniformity of the local interface region, leading to the rearrangement of some PU segments. Furthermore, excessively high concentrations may reduce the surface area of ​​nanoparticles effectively involved in interface regulation, causing some polymer segments to gradually revert to their original molecular arrangement, resulting in a rebound in the proportion of hydrogen-bonded carbonyl peak areas. In summary, the FTIR results show that the addition of OA@Fe3O4 nanoparticles did not change the main chemical structure of ISO2-PU, but it did establish certain interfacial interactions with the matrix.

[0105] 2. Characterization of the magnetic properties of OA@Fe3O4 / ISO2-PU composite material To evaluate the magnetic response properties of OA@Fe3O4 / ISO2-PU composites, saturation magnetization (Ms) was tested for composites with different OA@Fe3O4 addition ratios. The curves showing the change in magnetization with magnetic field strength are as follows: Figure 12 As shown in Table 4, the saturation magnetization test results are as follows.

[0106] Table 4 Saturation magnetization of composite materials With increasing OA@Fe3O4 content, the saturation magnetization of the OA@Fe3O4 / ISO2-PU composite gradually increased. When the OA@Fe3O4 content increased from 1 wt% to 15 wt%, the saturation magnetization of the composite increased from 0.67 emu / g to 13.19 emu / g, indicating that the introduction of magnetic nanoparticles can effectively endow the ISO2-PU composite with magnetic responsiveness. These results demonstrate that by adjusting the OA@Fe3O4 addition ratio, the magnetic properties of the OA@Fe3O4 / ISO2-PU composite can be controlled, resulting in different degrees of magnetic response characteristics. This provides a material basis for external magnetic field-driven microneedle structure deformation and active fixation.

[0107] 3. Compressive mechanical properties of OA@Fe3O4 / ISO2-PU composite material The compressive stress-strain curve is as follows: Figure 13As shown, all samples exhibited typical compressive deformation behavior of polyurethane elastomers. With increasing compressive strain, the material first undergoes an elastic deformation stage, followed by yielding and plastic adjustment stages, and finally exhibits significant strain hardening behavior. The compressive responses of composites with different OA@Fe3O4 contents showed significant differences, indicating that the introduction of magnetic nanoparticles can effectively modulate the mechanical behavior of the ISO2-PU matrix.

[0108] The compressive strength is shown in Table 5: Table 5 Compressive mechanical properties of composite materials The compressive strength of pure ISO2-PU material is 21.27 ± 0.20 MPa, exhibiting good compressive strength. With the OA@Fe3O4 content increasing to 10 wt%, the compressive strength of the composite material significantly improves to 26.80 ± 0.30 MPa. When the OA@Fe3O4 content is further increased to 13 wt% and 15 wt%, the compressive strength of the composite material decreases slightly. The high rigidity of Fe3O4 nanoparticles and the interfacial interaction between them and the ISO2-PU matrix are significant factors. During compression, the rigid Fe3O4 nanoparticles can bear part of the external load and restrict the slippage and local deformation of polyurethane molecular chains, thereby improving the material's resistance to compressive failure. However, under high filler conditions, the distance between nanoparticles decreases, and the interparticle interaction is enhanced, leading to increased local agglomeration and a reduction in the effective interfacial area. Simultaneously, excessive oleic acid flexible segments may increase the local compliance of the composite system, weakening the restrictive effect of rigid nanoparticles on polymer chains. Therefore, excessively high filler content reduces load transfer efficiency and limits the reinforcing effect.

[0109] In summary, the OA@Fe3O4 content has a significant regulatory effect on the compressive properties of ISO2-PU composites. Its reinforcing effect does not simply increase with the increase of filler content. Among them, the samples with OA@Fe3O4 content in the range of 3 wt%-13 wt% all showed good compressive strength, especially the sample with OA@Fe3O4 content of 10 wt% showed the best compressive strength, indicating that at this filler ratio, a better balance is achieved between the rigid nano-reinforcing effect, the oleic acid interface regulation effect, and the flexibility of the polyurethane matrix.

[0110] Example 2: Characterization of thermomagnetic response composite microneedles I. Morphology and Structural Characterization of Microneedles The composite microneedle structure prepared in Example 2 was characterized using optical microscopy and scanning electron microscopy (SEM). The results showed that... Figure 14As shown, the microneedle array obtained by hot pressing has a complete and uniform structure with regular needle morphology and no obvious collapse, breakage, or defects. The needle tip structure is clear and sharp, and the surface is continuous and dense, indicating that the composite material has good flowability and mold replication ability under hot pressing conditions. SEM results further show that the microneedle surface is flat and the structure is dense, with high sharpness in the needle tip area, which is beneficial to the realization of puncture performance. Overall results indicate that this process can achieve high-precision microscale structure replication, providing a stable structural foundation for subsequent functional applications.

[0111] II. Thermomagnetic Dual-Response Shape Memory Behavior like Figure 15 As shown, the thermomagnetic response performance of the composite microneedles was systematically tested. First, the initially bent microneedles were heated in an environment of 60 ℃ for 3 min to bring the material into a highly elastic state, at which point the polymer chain segment mobility was enhanced and the storage modulus decreased.

[0112] Under the influence of a gradient magnetic field formed by an external N52 neodymium iron boron magnet, the OA@Fe3O4 nanoparticles inside the composite microneedle generate a magnetic response torque, causing the microneedle to deflect directionally, gradually changing from a bent state to an upright state. After cooling to room temperature and holding at that temperature for 2 minutes while maintaining the magnetic field, the upright shape was successfully fixed. After the magnetic field was removed, the microneedle could still stably maintain its upright shape.

[0113] When the temperature was raised to 37 °C again, the material chain segments were reactivated, and the microneedles underwent shape recovery under entropic elastic driving force, eventually returning to their initial bent state, realizing a complete thermo-magnetic dual-driven reversible deformation process. The results show that the system has good programmable shape memory performance and long-range magnetic response capability.

[0114] III. In vitro biocompatibility evaluation 1. Blood compatibility Blood compatibility of the materials was evaluated using an in vitro hemolysis test. Physiological saline was used as a negative control, 0.25% Triton X-100 as a positive control, ISO2-PU and (PU)OA@Fe3O4 / ISO2-PU composite materials (15% OA@Fe3O4 and 15% PU) were used as experimental groups, and titanium clips (TTP) were used as a reference material. The supernatant of the experimental groups remained clear or light yellow and transparent, while the positive control was distinctly red. Figure 16 Quantitative analysis of the results showed that the hemolysis rates of both groups of materials were lower than the 5% limit specified in ISO 10993-4, and there was no significant difference, indicating that the introduction of OA@Fe3O4 did not have an adverse effect on the blood compatibility of the materials.

[0115] 2. Cell compatibility L929 cells were used to evaluate the in vitro cell compatibility of the materials. CCK-8 results are as follows: Figure 16As shown in b, cell viability in each group increased continuously with prolonged culture time. The OA@Fe3O4 / ISO2-PU group (OA@Fe3O4 addition of 15%) showed the same proliferation trend as the pure ISO2-PU group, and was slightly higher than the control group on day 3. P The OD values ​​were all above 2.8 on day 7 (<0.05), indicating that the material has good cell proliferation support ability.

[0116] Live / Dead staining results are as follows: Figure 16 As shown in Figure c, green fluorescent cells predominated in all groups, with only a small number of red cells observed, indicating a high cell viability. With prolonged culture time, the cells gradually proliferated and formed a continuous spreading structure, and no significant cytotoxicity was observed.

[0117] In summary, the OA@Fe3O4 / ISO2-PU composite microneedles achieve dual-driven deformation functions based on both magnetic and temperature responses while maintaining good structural integrity and biocompatibility. The material exhibits reversible shape memory properties under thermo-magnetic coupling, enabling programmable transitions between bent and upright states; furthermore, it demonstrates excellent biocompatibility in both in vitro blood and cellular environments.

[0118] The above results indicate that this composite system, possessing both microneedle structure functionality and magnetic response driving capability, has the potential to be used as an implantable smart biomedical material.

Claims

1. An application of a composite material microneedle, characterized in that, The microneedles are curved, and their shape and size parameters include: The microneedle consists of a cylindrical segment and a conical segment at the tip: the diameter of the cylindrical segment is 100 μm to 200 μm; the height of the cylindrical segment is 250 μm to 1500 μm; the height of the conical segment is 50 μm to 600 μm; and the angle between the axis of the microneedle tip and the base plane is 10° to 55°. The purpose of the microneedles is to prepare biodegradable CT-detectable implantable micro-devices for tumor target localization.

2. The use according to claim 1, characterized in that, The optimal parameters for the microneedle are: a cylindrical section diameter of 100 μm, a cylindrical section height of 750 μm, a conical section height of 150 μm, and an angle of 30° between the axis of the microneedle tip and the substrate plane.

3. The use according to claim 1, characterized in that, The microneedles are composed of the following components in parts by weight: 1-15 parts of oleic acid-modified iron oxide magnetic nanoparticles 85-99 parts of shape memory polyurethane material.

4. The use according to claim 1, characterized in that, The microneedles are composed of the following components in parts by weight: 3-13 parts of oleic acid-modified iron oxide magnetic nanoparticles 87-97 parts of shape memory polyurethane material.

5. The use according to claim 3, characterized in that, The shape memory polyurethane material is an amorphous polymer with a glass transition temperature of 37-45°C or a semi-crystalline polymer with a melting point of 37-45°C. It is composed of diisocyanate, soft segment polymer, and... A linear polymer polymerized at a molar ratio of 1.2-8 : 1 : 0.2-7, with a molecular weight of 30,000-150,000; The soft segment polymer is polylactic acid, polyglycolic acid, polycaprolactone, polypolyol, or a copolymer of two or more of these.

6. The use according to claim 5, characterized in that, The structural formula of the shape memory polyurethane material is shown in Formula I: Formula I Where x is selected from 1 to 10, and y is selected from 1 to 10; For the repeating unit of the soft segment polymer; It is a repeating unit of diisocyanate, or diisocyanate and The repeating unit of the copolymer.

7. The use according to claim 5, characterized in that, The soft segment polymer is a polymer of lactic acid and polyol; And / or, the structural formula of the soft segment polymer is shown in Formula II: Formula II Where m and n are independently selected from 4 to 50, and r is selected from 1 to 20.

8. The use according to claim 5, characterized in that, The diisocyanate is selected from aliphatic diisocyanates or aromatic diisocyanates. The aliphatic diisocyanate is selected from hexamethylene diisocyanate, lysine diisocyanate, isophorone diisocyanate, dicyclohexylmethane diisocyanate, or a mixture of two or more thereof. The aromatic diisocyanate is selected from toluene diisocyanate, diphenylmethane diisocyanate, or a mixture of two or more thereof.

Citation Information

Patent Citations

  • A shape memory polyurethane and a self-reinforcing regular porous polymer film thereof.

    CN114634608B